Improved method of building LTE network security segment - Одарченко, Р. С.; Мирутенко, Л.В.; Даков, С. Ю. (Science-based technologies, 2018)
The paper analyzes LTE technology, its features, general principles of construction on the basis of LTE / SAE wireless communication network, namely the design of a reference segment for maintenance of a large area. Were considered the possibilities of both modernization and network construction from scratch. For this purpose, LTE mobile network planning methods were analyzed. The optimal method of constructing a reference segment of the network is determined, which takes into account the cost of equipment for calculating the cost of deployment of the reference segment. The simulation of building a reference segment for the LTE network in the Kyiv region was performed. The cost of network equipment for this planning option is calculated.